Characterization of CdS0.9Se0.1powder by scanning transmission electron microscopy - Masahiro Kawasaki (2018)
© 2016, Chiang Mai Journal of Science. All Rights Reserved. n-type CdS0.9Se0.1powder was produced by mixing and annealing of CdS and Se powders that were prepared by a reflux method using Cd(CH3CO)2·2H2O, thiourea and ethylene glycol, and by a solution method using SeO2, ethylene glycol and NaBH4, respectively. The product was supposed to be crystalline CdS0.9Se0.1powder from simulation of X-ray diffraction pattern using CaRine 3.1 program and JCPDS card of CdS (space group P63mc). Analytical electron microscopy revealed that Cd, S and Se atoms were homogeneously distributed in the powder, which was composed of particles as fine as a few ten nm and in a single crystalline phase, supporting the formation of CdS0.9Se0.1. This CdS0.9Se0.1powder is expected to be used as n-type thermoelectric materials.